Treatment of Class I Kennedy lower jaw with precision attachment: Perawatan kasus Kelas I Kennedy rahang bawah dengan precision attachment - Melisa; Laura Susanti Himawan (Makassar Dental Journal PDGI Makassar, 2021)
Background: Rehabilitation of Kennedy Class I edentulous involves a variety of treatment alternatives such as overdenture, metal frame removable partial denture, RPD with precision attachment and implants. The combination of RPD and fixed dent-ture using precision attachment or semi-precision is one of the best forms of RPD. Case: A 59-year-old male came to the RSGM FKG UI clinic. He wants to have new denture to eat more comfortable and improve his appearance. Management: Anamnesis, extra-oral and intra oral examinations, and panoramic x-ray were performed. After that, bridge was removed, periapical x-ray and definitive treatment was determined using metal frame RPD in upper jaw and RPD with precision attachment in lower jaw. Conclusion: Patient feels satisfied and comfortable with his dentures both in upper and lower jaw with precision attachments.